Expanded programme of work on forest biological diversity versus IPF/IFF proposals for action - Thomas W. Schneider (Federal Research Centre for Forestry and Forest Products (BFH), Institute for World Forestry, 2004)
Since the United Nations Conference on Environment and Development (UNCED) in Rio de Janeiro in 1992, the international community entered a political dialogue on required actions for the promotion of management, conservation and sustainable development of the world's forests (all types of forests). The Commission on Sustainable Development (CSD) supported these intergovernmental negotiations by establishing the Intergovernmental Panel on Forests (IPF) in 1995 and the Intergovernmental Forum on Forests in 1997. The negotiations by IPF and IFF culminated in 2000 in the establishment1 of the International Arrangement on Forests (IAF) comprising the United Nations Forum on Forests (UNFF) and the Collaborative Partnership on Forests (CPF).
urn:nbn:de:gbv:253-200912-dk040082-0
Keywords: 630